If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-4=-2x+6
We move all terms to the left:
2x-4-(-2x+6)=0
We get rid of parentheses
2x+2x-6-4=0
We add all the numbers together, and all the variables
4x-10=0
We move all terms containing x to the left, all other terms to the right
4x=10
x=10/4
x=2+1/2
| 7-3k=1-3k | | 2x+x+4=19 | | -46t-23=46t+23 | | x2=9/400 | | 2x+7=5x-3(x-4) | | 10+x/4=22 | | 1x/2-9=7.5+6x | | -24=-4(2x-4) | | -11c+12c—15c-3c=-13 | | X^2+3+2x+4=15 | | 3x+216=2x | | k-3=7/9 | | 8k+4=8k | | 3(x+2(=-3x+6 | | -16+2=-2(x+8) | | 4(x+3)+10(x-3)=10 | | 4x=-8x+12 | | 6=(5+2x)(0.6) | | 6(2x+2)=4(3x-5) | | 46t-23=46t+23 | | 1/2(-3x^2-x)=0 | | 5p+8=6p | | |5x|=40 | | 45=12a-3 | | 4y+32=-3(y-6) | | 9x-27=-90 | | -7+x/3=-14 | | 3x+12-30=180 | | 2(a+3)=3(6a+2) | | x+1+2x-2=x+4 | | 6=(5+2x)(0.2) | | -4x+5x=-2 |